Effect of palm oil fuel ash on compressive strength of palm oil boiler stone lightweight aggregate concrete - Khairunisa, Muthusamy; N. A., Zamri; Andri, Kusbiantoro; N. H. A. S., Lim; M. A., Mohd Ariffin (IOP Publishing Ltd, 2018)
Both palm oil fuel ash (POFA) and palm oil boiler stone (POBS) are by-products which has been continuously generated by local palm oil mill in large amount. Both by products is usually disposed as profitless waste and considered as nuisance to environment. The present research investigates the workability and compressive strength performance of lightweight aggregate concrete (LWAC) made of palm oil boiler stone (POBS) known as palm oil boiler stone lightweight aggregate concrete (POBS LWAC) containing various content of palm oil fuel ash. The control specimen that is POBS LWAC of grade 60 were produced using 100% OPC. Then, another 4 mixes were prepared by varying the POFA percentage from 10%, 20%, 30% and 40% by weight of cement. Fresh mixes were subjected to slump test to determine its workability before casted in form of cubes. Then, all specimens were subjected to water curing up to 28 days and then tested for its compressive strength. It was found out that utilizing of optimum amount of POFA in POBS LWAC would improve the workability and compressive strength of the concrete. However, inclusion of POFA more than optimum amount is not recommended as it will increase the water demand leading to lower workability and strength reduction.